REGIONAL APPLICATION OF THE FIRST EUROPEAN AIR TRAFFIC CONTROLLER SELECTION TEST IN BULGARIA - Kharchenko, Volodymyr; Chynchenko, Yuriy; Raychev, Stefan (Proceedings of National Aviation University (archive), 2006)
Understanding Human Error in Air Traffic Control – the nature of human error was explored and the different types of error were clarified. The modelling of human error was explained and the most comprehensive approach within the Air Traffic Management system was described.